Firm Size, Firm Age, and Firm Profitability: Evidence from China - Md. Jahidur Rahman; Liu Yilun (STIE Malangkucecwara, 2021)
This study aims to investigate the relationship among firm size, firm age, and firm profitability in China’s stock market. We use data from all the public firms in China’s stock market from 2008 to 2018 and adopt a fixed effects model to examine these relationships. We find a positive relationship between firm size and profitability and a negative relationship between firm age and profitability, which is consistent with existing studies conducted in other countries. The findings of our study can contribute to future research in China by offering a sound basis and appropriate reference point, given that no previous research has been conducted in China on this exact topic. This study also offers a comprehensive model for use in future studies.